2017
DOI: 10.3892/mmr.2017.7940
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes, transcription factors and microRNAs involved in intracranial aneurysm

Abstract: Intracranial aneurysm (IA) is a devastating disease, the pathogenesis of which remains to be elucidated. The present study aimed to determine the molecular mechanism of IA and to identify potential therapeutic targets using bioinformatics analysis. The GSE54083 dataset, which includes data from patients with ruptured IA and superficial temporal artery controls, was downloaded from the Gene Expression Omnibus, and differentially expressed genes (DEGs) were identified in the ruptured IA samples using the limma p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Intracranial aneurysm (IA), also known as cerebral aneurysm, is caused by the increase of intracranial pressure induced by the local abnormal widening of the cerebral artery cavity or arterial wall [1]. IA is a severe disease with high mortality and morbidity, and the prevalence rate is about 1-3% in the general population [2].…”
Section: Introductionmentioning
confidence: 99%
“…Intracranial aneurysm (IA), also known as cerebral aneurysm, is caused by the increase of intracranial pressure induced by the local abnormal widening of the cerebral artery cavity or arterial wall [1]. IA is a severe disease with high mortality and morbidity, and the prevalence rate is about 1-3% in the general population [2].…”
Section: Introductionmentioning
confidence: 99%
“…Intracranial aneurysm (IA) is a kind of cerebrovascular disorder, which is featured by unconventionally bulged artery in the brain as well as subarachnoid hemorrhage (SAH) caused by IA rupture, accompanied with a high fatality and morbidity [1]. As is a destructive disease, the pathogenesis of IA has not been clarified [2]. IA is a rare familial form, but it is generally thought to be the result of acquired vascular injury caused by hypertension, smoking, and other traditional risk factors [3].…”
Section: Introductionmentioning
confidence: 99%
“…The enrichment analysis results showed that the 31 DEGs were mainly enriched in biological processes that related to immunity, such as “immune system process” and “immune response.” It has been reported in many tumor diseases where the tumor development was intimately correlated with the immune system process and the immune response 15, 16, 17. It has also been reported that there is an association between immunity and IA disease 18, 19. These results showed that there is a close relationship between the DEGs and the development of IA.…”
Section: Resultsmentioning
confidence: 56%